Pre-steady-state kinetic studies of redox reactions catalysed by Bacillus subtilis ferredoxin-NADP+ oxidoreductase with NADP+/NADPH and ferredoxin - Seo, Daisuke; Soeta, Takahiro; Sakurai, Hidehiro; Sétif, Pierre; Sakurai, Takeshi (Biochimica et biophysica acta, 2016)
Ferredoxin-NADP+ oxidoreductase ([EC1.18.1.2], FNR) from Bacillus subtilis (BsFNR) is a homodimeric flavoprotein sharing structural homology with bacterial NADPH-thioredoxin reductase. Pre-steady-state kinetics of the reactions of BsFNR with NADP+, NADPH, NADPD (deuterated form) and B. subtilis ferredoxin (BsFd) using stopped-flow spectrophotometry were studied. Mixing BsFNR with NADP+ and NADPH yielded two types of charge-transfer (CT) complexes, oxidized FNR (FNRox)-NADPH and reduced FNR (FNRred)-NADP+, both having CT absorption bands centered at approximately 600nm. After mixing BsFNRox with about a 10-fold molar excess of NADPH (forward reaction), BsFNR was almost completely reduced at equilibrium. When BsFNRred was mixed with NADP+, the amount of BsFNRox increased with increasing NADP+ concentration, but BsFNRred remained as the major species at equilibrium even with about 50-fold molar excess NADP+. In both directions, the hydride-transfer was the rate-determining step, where the forward direction rate constant (~500s−1) was much higher than the reverse one (<10s−1). Mixing BsFdred with BsFNRox induced rapid formation of a neutral semiquinone form. This process was almost completed within 1ms. Subsequently the neutral semiquinone form was reduced to the hydroquinone form with an apparent rate constant of 50 to 70s−1 at 10°C, which increased as BsFdred increased from 40 to 120μM. The reduction rate of BsFNRox by BsFdred was markedly decreased by premixing BsFNRox with BsFdox, indicating that the dissociation of BsFdox from BsFNRsq is rate-limiting in the reaction. The characteristics of the BsFNR reactions with NADP+/NADPH were compared with those of other types of FNRs.